Genotype and transcript processing of the tumour necrosis factor receptor TNFRSF1A in epithelial cells: implications for survival in cystic fibrosis - Uden, Alexander; Dunsche, Inga; Janciauskiene, Sabina; Gräber, Simon; Feng, Longhua; Tamm, Stephanie; Hedtfeld, Silke; Stege, Gesa; Jahn, Kirsten; Kontsendorn, Julia; Alfeis, Nadine; Kühbandner, Iris; et al. (EBioMedicine, 2025)
Background - Cystic fibrosis is caused by mutations of the cystic fibrosis transmembrane conductance regulator, CFTR, an epithelial anion transport protein, responsible for, inter alia, sputum viscoelasticity in the lung. We previously identified the TNF receptor superfamily 1A TNFRSF1A (TNFR1) as a genetic modifier of CFTR function and disease severity in the CF twin and sibling study population. We aimed to replicate our findings in independent cohorts, assess the role of TNFR1 for patient survival and identify functional changes associated with TNFR1 polymorphisms. - Methods - We incorporated data from three independent long-term mono- and multicentric cohorts of people with cystic fibrosis (pwCF) to confirm the previously described association of TNFR1 with CFTR function and to extend our study to include survival data for our local cohort and a pan-European cohort of pwCF. We studied TNFR1 transcripts obtained from primary airway epithelia grown as air-liquid interface cultures to address possible mechanisms involved in up-stream and down-stream effects of TNFR1. - Findings - Survival differed by more than a decade when comparing carriers of contrasting TNFR1 genotypes among unrelated pwCF as well as among CF siblings pairs. The presence of the TNFR1 transcript variant TNFR1delEx2 in primary airway epithelia was associated with TNFR1 genotype. - Interpretation - The association of the TNFR1 transcript variant TNFR1delEx2 associates with the TNFR1 genotype, possibly mediating the genotype-survival association we found regarding TNFR1 genotype and patient survival in cystic fibrosis. - Funding - Supported by the German Ministry for Education and Research (BMBF) (82DZL009B1 to MAM and 82DZL002A1, to GH, BT, AMD, FS) and the Mukoviszidose Institut gGmbH (MI-2002, to LN, AMD, FS).
Online verfügbar: 10. Juli 2025
Gesehen am 12.12.2025